Control your destiny or someone else will - Tichy, Noel M (HarperBusiness, 1994)
Originally published: New York : Doubleday, 1993; "Handbook for revolutionaries": p. [365]-448.; Includes bibliographical references and index; Neal A. Newfield, Ph.D., LICSW (Giver)